Strategic management of costs and isomorphism in micro and small companies from three sectors (Costos y Gestión, 2023)
Micro and small companies have very simple administrative and operational structures. Based on this premise, it is expected that their practices related to strategic cost management will be similar to each other, regardless of the sectors of economic activity of which they are part. The objective of this article is to investigate cost management practices among micro and small companies that operate in the commercial, industrial and service sectors in search of evidence of mimetic isomorphism. To carry out this research, ninety micro or small companies were analyzed. Four groups of variables were analyzed: managers' experience, marketing aspects, organizational aspects and technical aspects of strategic cost management. Data were collected from conducting a survey. Two statistical techniques were used: Kruskal-Wallis test and Mann-Whitney U test. The obtained results present significant statistical evidences about similarities concerning the practices related to cost management, indicating the presence of mimetic isomorphism between them.
Keywords: cost management; micro and small business management; institutional theory